Respuesta :

Answer = (g*h*f)(x) = 4x-3/x

Answer:

Option B - 6x-6/x

Step-by-step explanation:

Given : If [tex]f(x)=\frac{x-3}{x}, g(x)=x+3,h(x)=2x+1[/tex].

To find : What is the value of  [tex](g(h(f)))(x)[/tex]

Solution :

[tex](g(h(f)))(x)=g(h(f(x)))[/tex]

i.e, substitute the value of f(x) in h(x) and then put that h(x) in g(x).

[tex]g(h(f(x)))=g(h(\frac{x-3}{x}))[/tex]

[tex]g(h(f(x)))=g(2(\frac{x-3}{x})+1)[/tex]

[tex]g(h(f(x)))=(2(\frac{x-3}{x})+1)+3[/tex]

Solving the RHS,

[tex]=(2(\frac{x-3}{x})+1)+3[/tex]

[tex]=(\frac{2x-6}{x})+1)+3[/tex]

[tex]=(\frac{2x-6+x}{x})+3[/tex]

[tex]=\frac{3x-6}{x}+3[/tex]

[tex]=\frac{3x-6+3x}{x}[/tex]

[tex]=\frac{6x-6}{x}[/tex]

Therefore, The value of [tex](g(h(f)))(x)=\frac{6x-6}{x}[/tex]

Hence, Option B is correct.